2011
DOI: 10.3997/1873-0604.2011027
|View full text |Cite
|
Sign up to set email alerts
|

Informed experimental design for electrical resistivity imaging

Abstract: Electrical resistivity imaging has been successfully used to monitor near‐surface hydrologic processes but use of standard measurement arrays may not provide the greatest data sensitivity to the imaged region. We present a method of experimental design based on the concept of informed imaging for creating an electrical resistivity imaging experiment to monitor flow beneath a recharge pond. Informed imaging is the integration of all available data about a site into the acquisition, inversion and interpretation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Thus, it is not surprising that the detailed distribution of pools characteristic of a complex DNAPL may be challenging to resolve. Several methods can be used to provide optimum subsurface information, including informed ERT survey design (e.g., Nenna et al, 2011), and future work will explore these techniques in the context of DNAPL investigations. However, overall, Figure 6 suggests that, at favorable sites, ERT may be suitable for determining the outer boundaries of the location and depth of a DNAPL Figure 6.…”
Section: En10mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is not surprising that the detailed distribution of pools characteristic of a complex DNAPL may be challenging to resolve. Several methods can be used to provide optimum subsurface information, including informed ERT survey design (e.g., Nenna et al, 2011), and future work will explore these techniques in the context of DNAPL investigations. However, overall, Figure 6 suggests that, at favorable sites, ERT may be suitable for determining the outer boundaries of the location and depth of a DNAPL Figure 6.…”
Section: En10mentioning
confidence: 99%
“…Moreover, this envelope of favorable conditions is likely dependent on the ERT survey design and processing methodology, neither of which have been optimized for DNAPL sites. It is possible that recent advances in ERT imaging (e.g., data acquisition and timelapse monitoring) may be beneficial in this context (e.g., Ogilvy et al, 2009;Karaoulis et al, 2011a;Nenna et al, 2011). The systematic, controlled studies required to explore these questions at the field scale are not available from field trials or laboratory studies.…”
Section: Introductionmentioning
confidence: 94%
“…There have been many significant developments in algorithms to automatically select arrays to maximize the resolution of the inversion model for linear surface arrays and cross-borehole surveys (Stummer et al 2004;Wilkinson et al 2006aWilkinson et al , 2006bLoke et al 2010a;Nenna et al 2011;Hagrey 2012). A non-linear method that calculates the model resolution (the 'Compare R' method) by Wilkinson et al (2006b) proved to be the best method (Loke et al 2010a).…”
Section: Introductionmentioning
confidence: 99%
“…As a matter of fact, calculating the sensitivity in terms of homogeneous grounds is frequently used in practice to solve problems related to the DIC of resistivity arrays (e.g., Neukirch and Klitzsch, 2010;Nenna et al, 2011). For example, most of the algorithms for optimizing the survey design are based on sensitivity and current flow of homogenous ground (e.g., Furman et al, 2004;Stummer et al, 2004), and it has been found that the assumption of a homogeneous ground does not essentially limit the applicability of the optimized resistivity array (Stummer et al, 2004;Wilkinson et al, 2012).…”
Section: Discussionmentioning
confidence: 99%